Diagramme zwischen Metapher und Explikation : Studien zur Medien- und Filmästhetik der Diagrammatik - Ernst, Christoph (Präsenz und implizites Wissen ;, 2021)
Christoph Ernst develops the baselines of media and film aesthetics of diagrammatics - a trailblazing contribution to the contouring and further development of this field of research.